Pengembangan Kesenian Al-Banjari Sebagai Pelestarian Budaya Islam - Habibi, Wildan; Khaddaqotul Ulum, Ana; Agustina, Ayu; Hariroh, Linatul; Faizatul Uyun, Safira; Zuhri Nada, Siti (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2024)
This research was used to fulfill higher education PKM research assignments at the Faqih Asy’ari Islamic Institute. This type of research uses community service research (PKM). The aim of this research is to develop, advance and foster interest from within Tegalrejo village, to see that the progress of the banjari in Tegalrejo village, it self is considered to be advanced and developing well. The methods thah will be used in this research are observation and interviews. The aim of carrying out Hadroh Banjari religious activities is to strengthen the caracter values of the Tegalrejo community beyond those outside teh Tegalrejo Community a village where religious values are based. The stages of this research are : 1. Carrying out observations and visits to find problem points for which solutions will be sought, 2. Analyzing the problem, 3. Determining the purpose of our presence as researchers, 4. Consensusing the problem, 5. Approaching the community, 6. Assessment of the problem.